An industrial quality control study on engineering study on Alcos Global Corporation - Ereno, Bryan Donnel (College of Engineering, 2006)
Alcos Global Corporation started in the 1960's and is one of the oldest manufacturers of plastic products. Their clientele include large companies, come of which are Unilever, Avon and Wyeth. Due to the wide variety of the products and time constraints, the group only focused on the production of Wyeth's milk scoops. Data were gathered from the company through interviews, observations and reports. The problems regarding the production process of the said product line were determined using statistical problem solving tools. From the Pareto Chart, it was shown that among the defects, short shot handle and lips were the most probable reason for rejection. Next, possible causes of this defect were identified using the Ishikawa Diagram. The results showed that the dominating causes came from methods and machine issues. It was found out that the causes were due to machine error and irregularities of machine inspection. Problems in methods are minimal service options and insufficient process statistical documentation. The data was analyzed using Control Charts. The processes were found to be out of control. Yet, the group still performed Process Capability Analysis. Some Process Capability Ratios indicated process capability but some showed incapability. Alternatives were generated through brainstorming for the purpose of resolving the quality control problems. The alternatives are: 1) Utilize the use of control charts in monitoring milk scoops. 2) Install Statistical Process Control (SPC) software in the production line of Wyeth. 3) Initiate regular training scheme among quality personnel in innovations of control methods. 4) Make action plan for machine inspection and develop statistical documentation of machine process failure. 5) Perform experimental design study on the on the factors that have significant effects on machine-operator system 6) Suggest timely and more appropriate inspection at specific process points. 7) Eliminate hourly visual inspection and replace it with dimensional inspection. After the analysis of the alternatives, the group was able to come up with the best alternative, which is the use of control charts. To implement this, the Quality Control Personnel must be oriented with the use of the said statistical process tool. Implementation may take at least one week. Further studies regarding the evaluation of the currently employed acceptance sampling plan is recommended. If the sampling plan is found to be insufficient, a proposal of an appropriate plan can be suggested.